Penguatan Nilai Theo-Antroposentris Keislaman Mahasiswa UM Jember Masa Pandemi Covid 19 - Hairul Huda (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Having strong faith in the Almighty God and having a noble character are two sides ofelementary emphasis, having strong faith in the Almighty God is the embodiment of Islamic theosentry which tries to provide a point of emphasis on understanding God to students, while having a noble character is one ofthe emphases on the image of anthropocentric regarding the concept ofcollaborative behavior among human beings in this world. These two objectives are the most important parts of the national education system which is one of the roles of Islamic religious education in universities, both private and public. In the beginning, the learning process at UM Jember was held offline, but it has turned into online more recently. This study is based on a qualitative approach with a focus on collecting data on strengthening the theo-anthropocentric value of Islam through in-depth interviews. The data analysis process uses a triangulation model. The conclusions of this research are as follows: first, strengthening fundamental doctrine in Islamic Theo-Anthropocentric Students of UM Jember through two agendas, namely strengthening religion and social awareness; second, the strengthening of fundamental values in Islamic Theo-Anthropocentric students of UM Jember that can be seen from three activities, namely religious habituation, student interaction, attitudes and behaviors that are instilled in students.